Yield and response of soybean varieties to whitefly Bemisia tabaci (Genn.) in three planting dates - Cortez Mondaca, Edgardo; Pérez Márquez, Jesús; Rodríguez Cota, Franklin Gerardo; Martínez Carrillo, José Luis; Cervantes Cárdenas, Libnih (Revista Mexicana de Ciencias Agrícolas, 2018)
Planting date studies are important to help understand adaptation, behavior and plasticity of new plant materials in a given environment, under different management conditions and pressure of abiotic and biotic factors. During the spring-summer 2009-2009 was evaluated the agronomic behavior, phenology and response to whitefly of 12 soybean genotypes on three sowing dates in northern Sinaloa, Mexico. Treatments included six soybean varieties not evaluated in the region: AG 5605, AG 5903, AG 5905, AG 6301, AG 6702 and DB 6451; three commercial varieties Cajeme, Hector (Nainari) and Balbuena S-94; the variety Hutcheson highly preferred by white fly and two advanced lines from the National Research Institute for Forestry, Agriculture and Livestock candidates to new soybean varieties for the Northwest of Mexico: Cu04-139 and Cu04-238. The best genotype combinations by planting date in relation to grain yield were: CU04-139 with 2 496.1 and 2 442.9 kg ha-1  in the first and second planting date, Balbuena S-94; AG 6702 and AG 6301 with 2 360.8; 2 261.3 and 2 247.5 kg ha-1 in the first, third and second planting date respectively. The most preferred genotypes by adults and pupa of whitef ly are Hutcheson, DB 6451, AG 5905 and AG 6301. In contrast the less preferred varieties and less infested were Hector, CU04-238, S-94, Cajeme and AG 5903. The third planting date showed the greatest abundance of whitef lies.
Keywords: phenology; genotypes; whitefly; preference; resistance